The Two Worlds of Palliative Care: Bridging the Gap with Nepal - Sutcliffe, Simon B.; Bains, Puneet; Black, Fraser; Broughton, Sandra S.; Brown, Stuart; Colgan, Simon; Doherty, Megan E.; Fyles, Gillian; Love, Robin; Palat, Gayatri; Paudel, Bishnu; Russell, Charles; et al. (Nepal Journal of Science and Technology, 2021)
Despite past geo-political turbulence, Nepal has made significant progress in societal and economic initiatives, particularly in relation to social determinants of health. These improvements, however, belie the suffering of those with life-limiting disease due to pain, stigma, social and financial distress, consequent upon low patient, caregiver and health professional awareness of the need for, and availability of, appropriate care and support. Two Worlds Cancer Collaboration (INCTR-Canada) has been working with partners in Nepal to build capacity for palliative care by: (a) organizational and administrative support – establishing the Nepal Association of Palliative Care (NAPCare), and the creation of the Nepal Strategy for Palliative Care, approved by government in 2017; (b) “twinning” between 2 hospital palliative care units in Nepal and the Nanaimo Hospice and Victoria Hospice, BC, Canada; (c) sustainable growth of palliative care according to WHO foundational measures, implementing facility-based clinical programs, and home-based care aligned with the cultural, social, and economic environment of Nepal; (d) training of health professionals in adult and paediatricpalliative carethrough interactive on-line “distance learning” (Extension of Community Healthcare Outcomes, ECHO);(e) leveraging palliative care training and expertise across the government health system, and (f) local and international support to build a newfacility for Hospice Nepal to provide more support for more patients in a rural ambience on the outskirts of Kathmandu. Palliative care needs to become standard-of-care, providing peace, comfort and dignity for adults and children. Working collaboratively with partners in Nepal, the collective vision is a capable professional Nepali community leading palliative care services for all in need, wherever in need.